PERBEDAAN KUALITAS FISIK, BAKTERIOLOGIS, KIMIA PADA AIR PEMUKIMAN SEBELUMDAN SESUDAH DILAKUKAN PENYARINGAN DI DESA SANTUR KOTA SAWAHLUNTO TAHUN 2024 - Athosra, Athosra; Fatma, Fitria; Rianjati, Muarif (Universitas Fort De Kock, 2024)
Water plays a crucial role in life. The condition of residential water in Santur Village, Sawahlunto City was found to be murky, colored, and causing sediment in the water storage. This study aims to determine if there are differences in physical, bacteriological, and chemical quality of residential water before and after filtration in Santur Village, Sawahlunto City in 2024. The research uses an experimental design. The study population consists of residential water in Santur Village in July 2024, with treatments including filtration using gravel, sand, charcoal, coconut fiber, and foam. The results showed that, on average, before and after filtration: TDS was 316.8 before and 222.5 after; turbidity was 3.125 before and 0.00 after; color was 3.50 before and 0.00 after; E. coli was 105.8 before and 42.63 after; pH was 7.35 before and 7.07 after; Fe was 0.32 before and 0.07 after; Mn was 0.35 before and 0.08 after. The paired sample t-test and Wilcoxon signed-rank test showed significant differences in physical, bacteriological, and chemical quality of residential water before and after filtration with p-values as follows: TDS (p=0.017), turbidity (p=0.000), color (p=0.000), E. coli (p=0.816), pH (p=0.004), Fe (p=0.001), Mn (p=0.093). In conclusion, there are significant differences in the physical, bacteriological, and chemical quality of residential water before and after filtration using gravel, sand, charcoal, coconut fiber, and foam. This study is recommended as a consideration for policy-making by the government in residential water management.